'Not good enough:' Exploring self-criticism's role as a mediator between childhood emotional abuse & adult binge eating. (December 2016) - Feinson, Marjorie C.; Hornik-Lurie, Tzipi
Abstract: Empirical studies have identified emotional abuse in childhood (CEA) as a risk factor with long-term implications for psychological problems. Indeed, recent studies indicate it is more prevalent than behavioral forms of abuse, (i.e. childhood sexual and physical abuse) and the childhood trauma most clearly associated with subsequent eating pathology in adulthood. However, relatively little is understood about the mechanisms linking these distal experiences. This study explores three psychological mechanisms – self-criticism (SC), depression and anxiety symptoms – as plausible mediators that may account for the relationship between CEA and binge eating (BE) among adult women. Detailed telephone interviews conducted with a community-based sample of 498 adult women (mean age 44) assess BE, CEA and SC along with the most frequently researched psychological variables, anxiety and depression. Regression analyses reveal that BE is partially explained by CEA along with the three mediators. Bootstrapping analysis, which compares multiple mediators within a single model using thousands of repeated random sampling observations from the data set, reveals a striking finding: SC is the only psychological variable that makes a significant contribution to explaining BE severity. The unique role of punitive self-evaluations vis-à-vis binge eating warrants additional research and, in the interim, that clinicians consider broadening treatment interventions accordingly. Highlights: Childhood emotional abuse (CEA) is significantly related to binge eating (BE) Self-criticism (SC) is significantly associated with CEA and BE Mediation analyses reveal SC's unique contribution to BE severity Depression & anxiety do not make significant contributions to BE Unique role of SC should be considered in BE treatment strategies